Gloeocantharellus aculeatus (Gomphaceae), a new neotropical species in the gomphoid-phalloid clade - Linhares, Fernanda T. F.; Reck, Mateus A.; Daniëls, Pablo P.; Neves, Maria Alice (Phytotaxa, 2016)
Gloeocantharellus has an amphi-Pacific distribution, with five known neotropical species. Gloeocantharellus corneri was the only species in the genus recorded from Brazil. A new species, Gloeocantharellus aculeatus, was collected in the Atlantic Forest in the states of Espírito Santo and Santa Catarina of Brazil, and is described based on morphological and molecular characteristics. It is distinguished from other species in the genus by the orange to salmon pileus with slightly fibrillose margin, squamulose to pulverulent stipe, and aculeate basidiospores. The results of molecular analyses show that G. aculeatus is a distinct species and is closely related to G. corneri and G. echinosporus.